Procedural knowledge, decision making and performance in women's volleyball according to age group and specific experience - Flores Araujo, R. M.; Neves, J. A.; Ribeiro Mesquita, I. M. (The Open Sports Sciences Journal, 2012)
The purpose of this study was to analyze the procedural knowledge in action, decision-making and performance of the left-side attacker according to age group and specific experience, in women's volleyball. Four Portuguese women's teams participated in the present study: one under-16, one under-18 and two adult teams. A verbal interview protocol was implemented immediately after randomly chosen live game actions. The left-side attackers had to verbally respond to this question immediately following the execution of an attack, in 6 vs. 6 situations in practice. Players' decision-making and performance were analyzed by video images. Procedural knowledge was analyzed trough non-parametric statistics, namely Kruskal-Wallis and Mann-Whitney tests. Decision-making and performance were analyzed through Chi-square testing. Results showed that adult teams and the more experienced left-side attackers generated more goal concepts and fewer condition concepts, were more often concerned with the opponent and less with teammates. Moreover, no differences in player's performance and decision-making were observed according to age group and experience as left-side attackers. Further research should consider the characterization of the training process, mainly focusing on the tactical contents, as the information provided could provide a better and deeper understanding about the players' tactical development.